1982
DOI: 10.1037/0022-006x.50.3.448
|View full text |Cite
|
Sign up to set email alerts
|

Increasing cost-effectiveness in obesity treatment through use of self-help behavioral manuals and decreased therapist contact.

Abstract: Effectiveness and cost-effectiveness of a behavioral self-help manual for weight reduction were evaluated through the use of 126 community subjects. Over 10 weeks, four groups used the behavioral manual and four groups used an alternate manual under varying degrees of therapist guidance, and one group served as a delayed-treatment control. Results at posttreatment and 3-, 6-, and 16-month follow-ups supported the behavioral manual's effectiveness in producing modest weight loss. The manual could be applied und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Treatment involved eight weekly group sessions. Although the treatment was shorter than in many weight loss studies, significant weight losses can be produced by more focused formats (25, 26), and treatment length should not influence the effects of goals on weight loss.…”
Section: Research Methods and Proceduresmentioning
confidence: 96%
“…Treatment involved eight weekly group sessions. Although the treatment was shorter than in many weight loss studies, significant weight losses can be produced by more focused formats (25, 26), and treatment length should not influence the effects of goals on weight loss.…”
Section: Research Methods and Proceduresmentioning
confidence: 96%
“…Several researchers have specifically compared the use of varying degrees of therapist contact while controlling for other variables, such as the type of self‐help manual used and the total time spent in treatment. Pezzot‐Pearce and colleagues compared the use of a behavioural manual under therapist‐administered and self‐administered conditions (41). Significant weight losses resulted, with no increase in effectiveness in the two therapist‐administered conditions despite a fourfold and 20‐fold increase in cost and investment of therapist time.…”
Section: Effectiveness Of Self‐helpmentioning
confidence: 99%
“…For example, certain self‐help groups may be as effective as professionally administered clinical programmes, as discussed above. In addition, it is still unknown whether individual treatment is more effective than group therapy, and limited evidence has even suggested that it is less effective (41,42). Another problem related to the development of a stepped‐care approach to weight loss is that while many variations of treatment have been found to produce early weight loss, there still exists no well‐established treatment that produces permanent weight reduction.…”
Section: Stepped‐care Approachesmentioning
confidence: 99%
“…The efficacy of moderate intensity programs such as bibliotherapy has been reviewed previously (e.g., Rosen, 1987). Pezzot-Pearce, LeBow and Pearce (1982) found in the area of weight control that subjects who used a manual with minimal or no therapist guidance lost an average of 11 lbs by 6-month follow-up. Jeffery and Gerber (1982) also noted that subjects who participated in an active correspondence condition in the Minnesota Center of the Multiple Risk Factor Intervention Trial (MRFIT) maintained a 10-lb weight loss by 12-month follow-up.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%